Natural Regeneration of the Caatinga Detected Through NDVI in the Pedra da Andorinha Conservation Unit, Sobral - Ceará - Melo, Jakeline Oliveira; Nascimento Neto, José Nelson; Uchoa, Elenilton Bezerra; Rodrigues, Roberta Oliveira (Anuário do Instituto de Geociências, 2025)
The removal of native vegetation for human occupation and development of agropastoral activities end up making the local soil degraded. The Conservation Unit Refúgio De Vida Silvestre Pedra da Andorinha, located in the district of Taperuaba, municipality of Sobral, state of Ceará, is inserted in the Caatinga Biome, and due to the anthropic actions and the great importance of the biodiversity existing there was established as a protection area. This case study aimed to observe the process of natural regeneration in REVIS Pedra da Andorinha in the period from 1999 to 2019, with images from the Landsat series and using the Normalized Difference Vegetation Index (NDVI). Five classes of land use were established in order to obtain a visualization of land use both qualitatively and quantitatively and thus measure, in percentage terms, the gains and losses of vegetation within the space-time studied. The accuracy of the land cover classification was measured using the Kappa index. The results obtained showed that the study site presented a successful vegetative regeneration between the years 1999 and 2019. With a Kappa value of 1.0 and a Global Efficiency of 100%, the validation of the results showed equally excellent quality for both years, ensuring the reliability of the study. The present work highlighted the importance of the application of geoprocessing, performed through remote sensing, to be a tool of great potential for environmental analysis. The use of orbital images presents as advantages its ease and simplicity in obtaining the results, thus offering a better direction in the decision making of recovery and/or plant protection. REVIS Pedra da Andorinha presents few publications of studies, even with its landscape distinction. In view of this, this work is of fundamental importance for a source of research on the area.